What the children told us : the untold story of the famous "doll test" and the Black psychologists who changed the world - Spofford, Tim (Sourcebooks, 2022)
"Dr. Kenneth Clark visited run-down and under-resourced segregated schools across America, presenting Black children with two dolls: a white one with hair painted yellow and a brown one with hair painted black. "Give me the doll you like to play with," he said. "Give me the doll that is a nice doll." The psychological experiment Kenneth developed with his wife, Mamie, designed to measure how segregation affected Black children's perceptions of themselves and other Black people, was enlightening--and horrifying. Over and over again, the young children--some not yet five years old--selected the white doll as preferable and the brown doll as "bad". Some children even denied their race. "Yes," said brown-skinned Joan W., age six, when questioned about her affection for the light-skinned doll. "I would like to be white." What the Children Told Us is the story of the towering intellectual and emotional partnership between two Black scholars who highlighted the psychological effects of racial segregation"-- Dust jacket flap.